Gender Differences in the Attitude and Strategy towards Weight Control among Government Employees in Penang, Malaysia - Y Zaitun; MT Mohd Nasir; AS Hazizi; B Aina Mardiah; JM Hamid Jan (Tehran University of Medical Sciences, 2012)
"nBackground: This was a cross-sectional study on the gender differences in weight-control behavior. The strategies used, weight status, weight satisfaction, and proportion of individuals attempting to lose weight among 233 government employees (104 men and 129 women) working in the Federal Government Building in Penang, Malaysia, were assessed."nMethods: Anthropometric indicators such as body mass index, waist-to-hip ratio, and body fat percentage were measured to determine the subjects' body weight status. A questionnaire covering the following items was used to assess weight-control behavior: social support, self-monitoring, self-efficacy, outcome expectations, planning, preparation/buying, portion control, social interactions, and cognitive behavioral strategies."nResults: About 50% of the subjects were classified as overweight. Based on percent body fat percentage, 70% of them were classified as having unhealthy levels of body fat. Women were found to be more dissatisfied with their current weight, and were more likely to attempt weight reduction compared to men. Women reported higher levels of social support for dieting and had better expectations for diet and exercise (P < 0.05). They also reported higher use of weight control strategies. For self-monitoring, although no gender-dependent differences (P > 0.05) were observed, women reported more frequent self-monitoring of diet, whereas men reported more frequent self-monitoring of exercise."nConclusion: Health care professionals and researchers should be aware of the different strategies used by men and women in order to plan and/or implement community-wide weight management programmes.